The million dollar demise - Johnson, R. M. (Rodney Marcus) (New York : Simon & Schuster, 2009)
The main players in the soap-opera-style love triangle from "The Million Dollar Deception" and "The Million Dollar Divorce" continue their back-stabbing, duplicitous, and greed-marked relationships toward an unexpected conclusion.
Sequel to: The million dollar deception.
Keywords: African Americans -- Fiction; Triangles (Interpersonal relations) -- Fiction; Revenge -- Fiction